APLIKASI MOBILE SPEKTRA PADA PLATFORM ANDROID MENGGUNAKAN WEB SERVICES - Wongsonegoro, Jaceline; Wibowo, Adi; Handojo, Andreas (Jurnal Infra, 2013)
Petra Christian University Library, nowadays is using an information system to support the activities and services in the library. The information system provide services which able to be used by the user independently. However, some services are still required the help of the libraryâs staff. One of those services is order collection. The collection search service is not supporting storage of search results too, which needed by the user. By using widely used smartphone, an application is designed to overcome the weakness of the old information system and providing new services to the user.This application provides library collection search service where the selected search result can be saved in the cart. The other sevices are online journal access, favourite, reference note, rating, order collection, and comment. This application is designed to work on smartphone with Android operating system.Based on the testing result, this application is working properly on smartphone with Android operating system version 2.3 or Gingerbread in portrait orientation.